2018
DOI: 10.1007/s10549-018-4859-y
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of a breast surgery Enhanced Recovery After Surgery (ERAS) protocol to eliminate narcotic prescription at discharge

Abstract: A breast surgery-specific ERAS protocol employing opioid-sparing techniques successfully eliminated postoperative narcotic prescription without sacrificing perioperative pain control or increasing postoperative complications. By promoting the adoption of similar protocols, surgeons can continue to improve patient outcomes while decreasing the quantity of narcotics available for diversion within our patients' communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…Pain scores were evaluated at one day and one week postoperatively, and scores were reported on a 1-10 scale. They found no significant difference in pain scores for the ERAS vs. control group patients in surgeries including lumpectomy, sentinel lymph node biopsy, and axillary lymph node dissection at both postoperative Day 2 and Week 1 [3] .…”
Section: Enhanced Recovery After Surgerymentioning
confidence: 94%
See 2 more Smart Citations
“…Pain scores were evaluated at one day and one week postoperatively, and scores were reported on a 1-10 scale. They found no significant difference in pain scores for the ERAS vs. control group patients in surgeries including lumpectomy, sentinel lymph node biopsy, and axillary lymph node dissection at both postoperative Day 2 and Week 1 [3] .…”
Section: Enhanced Recovery After Surgerymentioning
confidence: 94%
“…Rojas et al [3] further implemented and reported outcomes on an ERAS protocol focused on breast surgery procedures with a goal of eliminating narcotic prescriptions after discharge. Their ERAS protocol used opioid-sparing techniques to eliminate narcotic prescriptions at discharge without sacrificing perioperative pain control.…”
Section: Enhanced Recovery After Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Although not intended to prevent opioid dependence, ERAS protocols should help by minimizing the need for narcotics for postoperative pain control. 22 In summary, ERAS is an effective, evidence-based tool widely embraced by other surgical subspecialties and with the potential to reduce opioid requirements of breast surgery patients. I congratulate the ASBrS for addressing the opioid crisis, providing these recommendations, and encouraging the adoption of ERAS pathways.…”
mentioning
confidence: 99%
“…A recent publication examining an ERAS pathway for patients undergoing breast-conservation surgery demonstrated successful elimination of postoperative narcotic prescriptions by employing the use of preoperative medications, including acetaminophen and gabapentin, local analgesia infiltration at surgery, and postoperative ibuprofen alternating with acetaminophen. 5 In addition, the importance of preoperative patient counseling to include the recommendation to utilize non-narcotic medications such as ibuprofen and acetaminophen first, and emphasizing that these medications alone may be enough to control postoperative pain, has been demonstrated to be critical in reducing the need for postoperative opioids after mastectomy. 6 A limitation of the present study is that data were not available to determine whether the subject group received less intravenous opioids not because they had adequate pain control with non-narcotic analgesics but because they were transitioned to oral opioids earlier than those in the control group.…”
mentioning
confidence: 99%